PENGARUH INOVASI DAN HARGA PRODUK TERHADAP PERILAKU PEMBELIAN SMARTPHONE BLACKBERRY DI WILAYAH JAKARTA BARAT - Tony Sitinjak, MM; Angeline SE (Jurnal Manajemen, 2011)
The intense competition among the cell phone companies push them to innovate their products. Nowadays, the most favorable cell phone in the society is Blackberry smart phone. In order to survive in the competition, Blackberry smart phones being innovative by offer new features and benefits. The prices are also varied according to the quality of its products. Being innovative and setting varied prices of Blackberry products aims to attract consumers to buy Blackberry smart phone. The research’s object is Blackberry smart phone. Data were collected by questionnaires which is distributed to two hundred respondents . Data analysis technique used is the percentage analysis, validity test, reliability test, and multiple linear regressions. The result of this research, there is a positive and significant influence between innovation and product prices on purchasing behavior of Blackberry smart phone.  So the research  conclusion is that innovation and product prices have an influence on consumers’ purchase behavior. To survive in the marketplace, companies have to sustainably innovate and promote their products to attract their consumers.  Keywords: innovation, product price, product quality, purchasing behavior.